Irrigation and crop diversification in the 25 de Setembro irrigation scheme, Mozambique - Sousa, Wilson, de; Ducrot, Raphaelle; Munguambe, Paiva; Bjornlund, Henning; Machava, Andre; Cheveia, Etevaldo; Faduco, Joaquim (Informa UK Limited, 2017)
Crop diversification is one way of improving the profitability of small-scale irrigation schemes. The 25 de Setembro scheme is an ideal site to analyze diversification, as it is influenced by the markets in Maputo and South Africa. This study uses information gathered from observations, discussions with irrigators and an irrigator survey. Results identified seven irrigator types with different crop diversification strategies predominantly influenced by resource constraints. Most irrigators produce traditional crops, although there are opportunities for growing crops that are more profitable. Improved extension services, to identify cropping strategies that better align with market demand, would improve profitability.